2015
DOI: 10.1167/iovs.15-17860
|View full text |Cite
|
Sign up to set email alerts
|

Nailfold Capillary Abnormalities in Primary Open-Angle Glaucoma: A Multisite Study

Abstract: PURPOSE. There is considerable evidence for systemic vascular dysfunction in primary openangle glaucoma (POAG). We performed nailfold capillary video microscopy to observe directly the nature of nonocular microvasculature abnormalities in POAG. METHODS.We enrolled 199 POAG patients and 124 control subjects from four sites. We used JH-1004 capillaroscopes to perform nailfold capillary video microscopy on the fourth and fifth digits of each subject's nondominant hand. Videos were evaluated for hemorrhages, dilat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
35
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 33 publications
(38 citation statements)
references
References 33 publications
3
35
0
Order By: Relevance
“…Previously we reported that 76.9% of 199 POAG patients had any hemorrhages using a protocol identical to the one used for this work. 21 Using an entirely new patient sample we observed that 71.3% of POAG patients had similar findings. In contrast, 60.8% of XFS/XFG had any hemorrhages.…”
Section: Discussionmentioning
confidence: 66%
See 2 more Smart Citations
“…Previously we reported that 76.9% of 199 POAG patients had any hemorrhages using a protocol identical to the one used for this work. 21 Using an entirely new patient sample we observed that 71.3% of POAG patients had similar findings. In contrast, 60.8% of XFS/XFG had any hemorrhages.…”
Section: Discussionmentioning
confidence: 66%
“…We speculated that impaired nitric oxide signaling might be responsible for nailfold hemorrhages in POAG. 21 Interestingly, some 51,52 but not all studies 53 show that asymmetric dimethyl arginine, an inhibitor of nitric oxide synthase and contributor to endothelial cell dysfunction, is elevated in the aqueous humor and serum of XFS/XFG patients. One needs also to consider that other mechanisms may be operative in the formation of nailfold hemorrhages in XFS/XFG including a tendency for inherent blood clot formation as demonstrated by rotational thromboelastography.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Pasquale et al. () studied the relationship between nailfold microvascular abnormalities and POAG. In that study, investigators found a 12‐fold increased risk of POAG in association with nailfold haemorrhages indicating systemic vascular abnormalities.…”
Section: Discussionmentioning
confidence: 99%
“…; Pasquale et al. ). Specifically, reductions in retinal, choroidal and retrobulbar blood flow and impairment in vascular autoregulation (Flammer et al.…”
Section: Introductionmentioning
confidence: 98%